2020
DOI: 10.7883/yoken.jjid.2019.111
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nontuberculous Mycobacteria from Clinical Isolates and Specimens using AdvanSure Mycobacteria GenoBlot Assay

Abstract: The aim of this study was to evaluate the clinical performance of AdvanSure GenoBlot assay using NTM isolates and clinical specimens. A total of 136 NTM isolates and 176 clinical specimens were included in this study. AdvanSure Mycobacteria GenoBlot assay was performed according to the manufacturer's instructions. We compared the results with those of 16S rRNA and rpoB genes sequencing. Of the total 136 isolates, 111 (81.6%) were correctly identified to the species level by the GenoBlot assay. The final concor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In addition, there is no gold standard for detection and identification of multiple species infection of NTM. LPA and multiplex real-time PCR/melting curve analysis have been applied to detect mixed infections with different NTM species based on the 16S-23S rRNA intergenic transcribed spacer (ITS) region and achieved good performance using material directly from clinical samples [ 16 , 17 , 18 ]. However, the resolution of these techniques is still low because not all NTM species, especially newly discovered species, have not been included in assay development.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is no gold standard for detection and identification of multiple species infection of NTM. LPA and multiplex real-time PCR/melting curve analysis have been applied to detect mixed infections with different NTM species based on the 16S-23S rRNA intergenic transcribed spacer (ITS) region and achieved good performance using material directly from clinical samples [ 16 , 17 , 18 ]. However, the resolution of these techniques is still low because not all NTM species, especially newly discovered species, have not been included in assay development.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other assays, the CapitalBio Mycobacterium identification array system shows higher sensitivity and specificity. 36 It has been reported that the sensitivity and specificity of the CapitalBio Mycobacterium identification microarray system were 99.6% and 100%, respectively, compared with the results of 16S rRNA gene sequencing when used with clinical isolates from respiratory specimens. 16 Interestingly, it can identify up to 17 Mycobacterium species.…”
Section: Discussionmentioning
confidence: 99%
“…NTM species identification was performed using the AdvanSure Mycobacteria GenoBlot assay (LG Chem) at KIT. The assay can identify Mycobacterium tuberculosis complex and 20 different NTM species 24 . The reverse line probe assay can detect the presence of ≥2 NTM species infection in a single specimen.…”
Section: Mycobacterial Culture Identification and Antimicrobial Susce...mentioning
confidence: 99%